PENGARUHDISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT.SEKAR MULIA ABADI MEDAN - Nurmaidah Br Ginting (UII, 2018)
PT. Sekar Mulia Abadi is a company engaged in the fruit import distributor which has a subsidiary in Pekan Baru. The problems that occur in PT. Sekar Mulia Abadi were relating to the work discipline and communication. Employees were often absent and arriving late and communication between supervisors and subordinates were less effective that employee's performance declined, characterized by decreased sales target so that the company's goal was not achieved. Based on the brief description, the problem formulated in this study as the followings; how is the effect of labor discipline and communication on employes performance at PT. Sekar Mulia Abadi Medan.The theory used in this research are theories of human resource management related to work discipline, communication and employee performance.The method used in this research is quantitative, this kind of research is quantitative descriptive, and the nature of this research is descriptive explanatory. Data collection was performed by interviews, questionnaires, and documentation study. Data analysis method used is multiple regression analysis. The population in this study were all employees of PT. Sekar Mulia Abadi field totaling 102 respondents, of which 30 respondents were used to test the validity and the remaining, 72 respondents were used as samples.Results of the study showed that the hypothesis r 0248 on a unit o work discipline and 0,461 were units of communication which partially has a significant effect on employee performance and simultaneously there is a significant effect of the two variables by 26.2% on employee performance at PT. Sekar Mulia Abadi Medan and the remaining 73.8% is explained by other variables not examined in this study.The study concluded that the simultaneous and partial discipline of work and communication have a significant effect on the performance of employees at PT. Sekar Mulia Abadi field.